Variation in community intervention programmes and consequences for children and families: the example of Sure Start Local Programmes. - Melhuish, E; Belsky, J; Anning, A; Ball, M; Barnes, J; Romaniuk, H; Leyland, A (2007)
BACKGROUND: An area-based initiative, Sure Start Local Programmes (SSLPs), was established by the UK government to reduce social exclusion through improving the well-being of children aged 0-3 years and their families in disadvantaged communities; a true community intervention in that all children under four and their families in specified areas served as targets of universal services. A national evaluation examined the links between variation in programme implementation and effectiveness. METHODS: Data gathered from multiple sources produced measures of implementation in terms of proficiency, services and staffing. Measures of programme impact on child/parenting outcomes derived from multilevel models, controlling for child, family and area characteristics, were identified to demonstrate programme effectiveness. RESULTS: Some modest linkage between programme implementation (e.g., proficiency, empowerment of parents and staff, identification of users) and effectiveness for child and parenting outcomes. CONCLUSIONS: Overall proficiency and specific aspects of implementation may influence effectiveness, which should guide the design of other child, family and community services.